Experimental investigation of 3D woven Cu lattices for heat exchanger applications. (May 2016) - Zhao, Longyu; Ryan, Stephen M.; Ortega, Jeanette K.; Ha, Seunghyun; Sharp, Keith W.; Guest, James K.; Hemker, Kevin J.; Weihs, Timothy P.
Highlights: Investigation of fluidic and thermal properties on 3D woven Cu lattice materials. Characterization of pressure drop, heat transfer and temperature uniformity. Various lattice architectures, flow patterns and coolants are studied. Comparison to other heat dissipation media in multiple performance indices. Multi-functional heat exchanger with load bearing and energy absorption capabilities. Abstract: Stochastic metallic foams and periodic porous media have been used extensively in heat transfer applications. A relatively new cellular material, 3D woven Cu lattices, show potential for increased thermal performance, due to their high specific surface areas, high thermal conductivity and regular micro-pore distributions. This work investigates the performance of these lattices in both a "standard" and a topology "optimized" architecture using three flow patterns (axial, focused bifurcated and full bifurcated) and two working coolants (water and air). We characterize and compare three performance metrics: pressure drop, average surface temperature and temperature uniformity for the various lattices, flow patterns, and coolants. The optimized weave shows lower pressure drops but higher average surface temperatures and higher temperature variations compared to the standard weave for all flow patterns and both coolants. The bifurcated flow patterns demonstrate lower pressure drops and lower temperature variations but higher average surface temperatures compared to the axial flow pattern for the two weaves and coolants. We also compare the fluidic and thermal performance of the weaves to other common heat dissipation media using the axial flow pattern and both coolants by plotting friction factors, Nusselt numbers and thermal efficiencies as a function of Reynolds numbers that range from 3 to 125. The standard and optimized weaves exhibit relatively high values in flow resistance and heat transfer, and similar values in thermal efficiency compared to other heat exchangers when using water or air. In addition, the weaves provide excellent temperature uniformity in the bifurcated flow patterns, suggesting they are great candidates for applications requiring both high heat removal and uniform temperature distributions such as the cooling of high power laser diodes.